2021
DOI: 10.3390/f12111469
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Activity of Soils Forming on an Afforested Heap from an Opencast Sulphur Mine

Abstract: Post-mining areas require reclamation. The main aim of reclamation is to restore the soil as a basic element of the terrestrial ecosystem. This paper presents the results of an evaluation of the enzymatic activity of soils formed on an afforested heap from an opencast sulphur mine. Six research sites were selected on the overburden heap of the Piaseczno sulphur mine, afforested 50 years ago. They differed in the type of soil in the subsoil and in the species composition of the stand. The activity of dehydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 90 publications
(94 reference statements)
1
6
0
1
Order By: Relevance
“…At the end of the study, the TOC content was significantly higher in soil treated with SSFAC. The results obtained confirm the thesis known from the literature that, in soil reclamation, the introduction of external organic matter and its quality are important for organic matter accumulation processes [104]. With a dose of 180 Mg•ha −1 SSC, more TOC was introduced into the soil than with SSFAC.…”
Section: Discussionsupporting
confidence: 87%
“…At the end of the study, the TOC content was significantly higher in soil treated with SSFAC. The results obtained confirm the thesis known from the literature that, in soil reclamation, the introduction of external organic matter and its quality are important for organic matter accumulation processes [104]. With a dose of 180 Mg•ha −1 SSC, more TOC was introduced into the soil than with SSFAC.…”
Section: Discussionsupporting
confidence: 87%
“…The increase in soil enzyme activity is parallel to the increase in soil organic matter. This situation reveals that enzymes are linked to the population dynamics of the soil biota (Myszura et al, 2021). It is reported that the increase in urease activity with the addition of organic matter to the soil is mainly attributed to the nitrogen content of the added material (Piotrowska-Długosz et al, 2022).…”
Section: Urease Activitymentioning
confidence: 97%
“…In the soil, non-specific (carbohydrates, phenols, amino acids, fats, alcohols, etc.) and specific (humus substances) organic compounds can act as substrates [48,49]. Dehydrogenases act as catalysts for a wide range of oxidative reactions that are associated with the degradation of soil organic matter [50].…”
Section: Biological Indicatorsmentioning
confidence: 99%